PENINGKATAN SELF EFFICACY SISWA KELAS X MAN 4 MARTUBUNG MEDAN DENGAN MENGGUNAKAN MODEL PEMBELAJARAN BERBASIS MASALAH - Anugrah Mulia Tampubolon (State Islamic University of North Sumatra, 2019)
The purpose of this research was to identify the inprovement of student's Self Efficacy as an impact of problem based learnin, asd to find the interaction between the instructional approach and gender with improvement of student's Self Efficacy. This research was a quasy experiment with the sample of research was 70 students, consisted of X-IPA2 with 35 students asan experiment class and X-IPA4 with 35 students as a control class. The data which collected in this research were Self Efficacy. The instruments which used to collect the data were a test of Self Efficacy. The data were analyzed by using two way anava in the SPSS program. Based on the result of this research, it could be concluded that the improvement student's Self Efficacy by using problem based learning better than improvemet student's Self Efficacy by using a usuall learning. There was not an interaction between the instructional approach and gender with improvement student's Self Efficacy.